Trade Policy Flexibilities and Turkey : Tariffs, Antidumping, Safeguards, and WTO Dispute Settlement - Bown, Chad P. (World Bank, Washington, DC, 2013)
Trade policy commitments to lower import tariffs and to maintain tariffs at low levels entail short and long-run political-economic costs and benefits. Empirical work examining the relationship between such commitments and the exercise of trade policy flexibilities is still relatively nascent, especially for emerging economies. This paper provides a rich, empirically-based assessment of ways that Turkey exercised trade policy flexibilities during the global economic crisis of 2008-11. First, and despite multilateral and customs union commitments that might limit changes to applied tariffs, Turkey made changes to both its applied Most Favored Nation and preferential tariffs that cumulatively affect nearly 9 percent of manufacturing imports and 10 percent of import product lines. Second, Turkey's cumulative application of temporary trade barrier (TTB) policies -- antidumping, safeguards and countervailing duties -- are estimated to impact by 2011 an additional 4 percent of imports and 6 percent of product lines. Other surprising results on Turkey's use of flexibilities include: extending the duration of previously imposed antidumping and safeguards beyond expected removal dates, removing one TTB policy over a set of products and immediately reapplying a different TTB policy, covering lengthy upstream and downstream segments of important industries, and deepening discriminatory preference margins already inherent in existing preferential trade agreements.